Reliability and validity of the problematic TikTok Use Scale among the general population - Günlü, Aykut; Oral, Tuncay; Yoo, Soyoung; Chung, Seockhoon (Frontiers in Psychiatry, 2023)
Introduction This study aims to provide a scale for measuring problematic TikTok use levels by adapting items from the Instagram Addiction Scale. Methods The 372 participants were determined by a convenience sampling method, and data were collected through Google online forms. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were performed for construct validity and criterion-related validity analysis. Criterion-related validity for the problematic TikTok use scale (PTTUS) was tested using correlation analysis between the Bergen Social Media Addiction Scale and Social Media Use Disorder Scale. Results EFA indicated that a three-factor structure should be formed. The first factor is the sub-dimension of obsession and consists of 4 items, the second factor is the escapism sub-dimension and consists of 6 items, and the third factor is the lack of control sub-dimension and consists of 6 items. The model fit for adapting the PTTUS into Turkish was examined with first-level CFA, χ2/sd, RMSEA, CFI, GFI, AGFI, and SRMR, the obtained values show that the three-factor structure of the scale provides acceptable fit. Reliability analyses showed that Cronbach's alpha internal consistency reliability coefficient ranged from .83 to .90; McDonald’s Omega reliability values was .84 to .90, and test-retest correlation coefficient ranged from .68 to .73, indicating sufficient internal consistency and test-retest reliability. Conclusions Based on this information, PTTUS is a measurement tool with sufficient psychometric properties that can be applied to determine individuals’ levels of problematic TikTok use.